The Effects of Retirement’s Self-perceived Health status and Interaction with Close People on the Quality of Life - Shim, Da-Yeon; Park , Su-Sun; Park , Su-Sun (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study is designed to investigate the conscious mental health and social exchanges affecting the quality of life by selecting retirees over the last three years. Methods/Statistical analysis: This study used the 6th year data collected in 2016 among the Korean Longitudinal Study of Aging (KLoSA) data. The collected data were analyzed using the SPSS statistics program. The data analysis procedure was first, T-Test and ANOVA analyses were conducted. Second, multiple regression analysis was conducted to examine the effects of Self-perceived health status and interaction with close people on overall quality of life. Findings: First, The overall quality of life was founded significantly higher on the case of higher the final education of female than male, case of married to a spouse compared to no spouse case, and the case of higher the household income. Subjective health satisfaction Model 2’s regression equation that looking at the effects of subjective health satisfaction and the degree of interaction with close people on the quality of life was also found to be significant, and it has an explanation ability of 28.3%. Among the socio-demographic variables, the overall quality of life was founded significantly on the case of higher the final education of female than male and case of married to a spouse case compared to no spouse case. Subjective health satisfaction the higher the subjective health satisfaction, and the higher the degree of interaction with close people were founded as the higher the overall quality of life. Improvements/Applications: We will have to approach with caution in future programs and institutions for retirees so that they can maintain social networks before retirement and gradually practice social adaptation.